Guinness world records 2005 - Herndon, Ryan. (New York : Bantam Books, 2005)
1. World records.--Periodicals. 2. Curiosities and wonders--Periodicals.
Basic ed. students
Keywords: Animals -- Miscellanea; Pets -- Miscellanea